La politique de la sociologie : coopération et implication dans le texte sociologique - Danny Trom (Tracés, 2013)
This paper characterizes sociology as a form of knowledge of society about itself. It asks what makes sociological texts successful when evaluated by the community of sociologists. In order to answer this question, sociological texts are examined through the cooperative work which connects the author and the readers in the act of reading. Based on a case study, the paper shows that an implicit pact governs their relationship. In exploring what this implicit pact consists in, it comes to the conclusion that a political frame underlies the production-reception of the text. This pact delineates a mode of implication of the reader in a text and organizes the modalities of this implication. Making this pact explicit as well as the entailed implication, means intensifying the reflexivity of sociology itself.